Stepped Care 2.0: The Power of Conundrums - Cornish, Peter; Berry, Gillian (Cham : Springer International Publishing : Imprint: Springer, 2023)
Stepped Care 2.0: A Paradigm Shift in Mental Health, by Dr Peter Cornish, made a compelling argument for why the existing mental health care system has consistently struggled to meet the needs of clients from all walks of life, and laid out key principles and guidelines for how the system could be changed. But what challenges are involved in putting these ideas into practice? Stepped Care 2.0: The Power of Conundrums features essays, interviews, and arguments from a wide range of contributors who have tried to do just that. The Power of Conundrums dives deep into the practical application of the Stepped Care 2.0 model (SC2.0), looking at the ways SC2.0 has succeeded, the difficulties administrators face when implementing it, and how it could be improved. Chapters touch on topics including: the evidence for stepped care, the way SC2.0 can be stymied by the Western cultural values that dominate mental healthcare, implementation science and SC2.0, the riskparadigm and SC2.0, the model's one-at-a-time approach to therapy, what co-design means in an SC2.0 context, a case study on how implementing SC2.0 can go wrong, the understanding of recovery put forward by the model, and how SC2.0 can work for clients experiencing complex, persistent, or chronic mental health issues. Each chapter is followed by a reflection from Cornish, and the book concludes with a roundtable discussion about how SC2.0 can evolve to meet the challenges it faces. This text brings theory and practice together by including an updated version of Stepped Care 2.0: A Paradigm Shift in Mental Health, as well as the full text of Stepped Care 2.0: The Power of Conundrums.
Chapter 1 -- The Promise of Stepped Care 2.0; Chapter 2 -- Stepped Care Research Findings: A Dog's Breakfast or Enough to Move Forward?; Chapter3 -- Even our Lawyers Have Lawyers: Why Shifting the Risk Paradigm in Mental Health Care is So Hard; Chapter 4 -- The Great Debate 2.0: Evidence-Based Practice vs Practice-Based Evidence; Chapter 5 -- Why Stepped Care 2.0 Won't Work (But it Might the Best We Can Do); Chapter 6 -- Identifying "The System" Flaws or "Necessity is the Mother of Invention"; Chapter 7 -- One is Enough. Or is It?; Chapter 8 -- To Declare or Not: Can SC2.0 Present Real Choices for Those with Disabilities?; Chapter 9 -- Stepped Care 2.0 in Motion: Adaptations of a Model, or Principles for Organic Local Design; Chapter 10 -- Conclusion: From What to How: The Need for Knowledge Mobilization and Implementation Science.
Keywords: Clinical health psychology; Therapeutics; Behavior genetics; Psychiatry; Counseling; Neuropsychology; Health Psychology; Therapeutics; Behavioral Genetics; Psychiatry; Counseling Psychology; Neuropsychology